Transactions of minors in English and German law - Brunold, CF (2022)
This thesis is a comparative analysis of the ability of minors in English and German law to enter into and perform transactions, as well as of the protection that each jurisdiction provides them with. The core insight that this thesis offers is a better understanding of what the ‘protection of minors’ from improvident transactions means in each of the two jurisdictions by determining the underlying policies. English law allows minors to enter into and perform transactions and thereby dispose of their property. Minority bars only the enforcement of minors’ promises, whether directly or indirectly in tort or unjust enrichment, and subject to certain exceptions. By contrast, German law limits minors’ ability to participate in transactions autonomously nearly completely and confers all control over minors’ transactions on their parents. The latter can even act on behalf of their child as agents by statute and make their child party to transactions without the latter knowing. This thesis analyses the impact that ‘minority’ has in the areas of contract, (personal) property, and restitution of unjust(ified) enrichment in light of these policies. Following the far-reaching powers of parents over their children, a further important point of consideration in this thesis is the role which parents and the state play in protecting minors from improvident bargains. It can be shown that parents are generally in a fiduciary position in relation to their children and their property and are personally liable for breaches of duty in this regard. A proposal for English and German law to improve the protection of minors from misappropriations of their property by their parents is discussed in this context. In addition, the thesis assesses further particularities of English and German law concerning ‘minority’, such as the abstract design of German law versus the flexible and individualised approach taken in England.